Evaluating the Impact of Payroll Fraud on Organizational Performance Case study of Stanbic Bank-Head Office - Bernadette Ilunga Nkulu (Uganda Christian University, 2024)
The influence of payroll fraud on organizational performance: a case of Stanbic Bank-Head office. The general purpose of this research is to establish the influence of payroll fraud on ghost workers, false wage claims, and false expense claims. Pursuing the objectives of this research, a survey design was undertaken and questionnaires with 5-point Likert summated rating scales were used. It was analyzed based on multiple regression analysis, and it has identified the result that ghost workers, false expense claims, and false wage claims are found to be the major factors affecting the organizational performance at Stanbic Bank- Head office. Increase in ghost workers negatively affects the organizational performance of Stanbic Bank but not significant when measured against the false expense claims and false wage claims. This means that Stanbic Bank may not grow into developing the potential to help reduce or eradicate unemployment if pragmatic decisions are not taken concerning this. The findings of the paper concluded that proper management of variables on payroll fraud should be encouraged in the Bank.